Pocock, Machiavelli and Political Contingency in Foreign Affairs: Republican Existentialism Outside (and Within) the City. Issue 2 (17th February 2017) - McCormick, John P.
SUMMARY: In this essay, inspired by J.G.A. Pocock's appropriation of Machiavelli's theory of political contingency, and building upon my previous engagements with Pocock's 'republican existentialism', I focus on the role played by 'accidents' in Machiavelli's analysis of war and foreign affairs within The Prince and the Discourses . In so doing, I consider the following issues: the ways through which a potential imperial hegemon might consolidate control over nearby lesser powers—and, conversely, how such less powerful polities might resist imperial encroachments on their autonomy; the contrasting military modes and orders characteristic of ancient and modern republics; and the extent to which Machiavelli actually thought that accidents in foreign affairs were ever truly 'accidental' in light of his determinations concerning well- versus badly ordered domestic institutions.